Advances in the Critical Care Management of Ischemic Stroke - Vineeta Singh; Nancy J. Edwards (Stroke Research and Treatment)
Given recent advances in diagnostic modalities and revascularization capabilities, clinicians are not only able to rapidly and accurately identify acute ischemic stroke, but may also be able to aggressively intervene to minimize the extent of infarction. In those cases where revascularization cannot occur and/or the extent of infarction is large, there are multiple strategies to prevent secondary decompensation as the stroke evolves, for instance, if malignant cerebral edema should develop. In this paper, we will review the indications for specialized ICU care for an ischemic stroke patient, the treatment principles, and strategies employed by neurointensivists to minimize secondary neuronal injury, the literature in support of such strategies (and the questions to be addressed by future studies), all with the ultimate goal of increasing the likelihood of favorable neurologic outcomes in our ischemic stroke population.